Substituted 2-hydroxy-N-(arylalkyl)benzamide sensitizes cancer cells to metabolic stress by disrupting actin cytoskeleton and inhibiting autophagic flux - Páchniková, Gabriela; Uldrijan, Stjepan; Imramovský, Aleš; Kryštof, Vladimír; Slaninová, Iva (Toxicology in vitro, 2016)
N-((R)-1-(4-chlorophenylcarbamoyl)-2-phenylethyl)-5-chloro-2-hydroxybenzamide (Compound 6k), was recently isolated during the preparation of amino acids esters with salicylanilides. We show here that 6k disrupts the dynamics of actin cytoskeleton in human melanoma cells, affecting processes essential for the maintenance and expansion of tumours such as cell adhesion, motility, proliferation, vesicular transport, and autophagic flux. We demonstrated that inhibition of autophagy by 6k increased the sensitivity of melanoma cells to metabolic stress induced by rotenone or nutrient starvation and potentiated the anti-proliferative activity of small molecule multikinase inhibitor sorafenib. Since autophagy plays an important role in survival of cancer cells subjected to chemotherapy, the above mentioned properties are interesting from clinical point of view as 6k could promote metabolic stress within the tumour microenvironment and potentiate the effect of cytostatics in combination therapy.
Keywords: Stress, Physiological; proliferace buněk; apoptóza; Metabolic stress; mikrofilamenta; buněčné linie; Autophagy; inhibitory proteinkinas; Cell Line, Tumor; Phenylalanine; Apoptosis; Cell Cycle; Wound Healing; lidé; niacinamid; Antineoplastic Agents; protinádorové látky; Actin; Niacinamide; fenylmočovinové sloučeniny; fyziologický stres; Cell Line; buněčný cyklus; autofagie; Benzamides; fenylalanin; Protein Kinase Inhibitors; benzamidy; hojení ran; Cell Proliferation; sorafenib; Substituted 2-hydroxy-N-(arylalkyl)benzamide; Phenylurea Compounds; Sorafenib; Actin Cytoskeleton; nádorové buněčné linie; Melanoma; Humans